The aeromicrobiome: the selective and dynamic outer-layer of the Earth’s microbiome - Amato, Pierre; Mathonat, Frederic; Nuñez Lopez, Leslie; Péguilhan, Raphaëlle; Bourhane, Zeina; Rossi, Florent; Vyskocil, Jonathan; Joly, Muriel; Ervens, Barbara (Frontiers in Microbiology, 2023)
The atmosphere is an integral component of the Earth’s microbiome. Abundance, viability and diversity of microorganisms circulating in the air are determined by various factors including environmental physical variables and intrinsic and biological properties of microbes, all ranging over large scales. The aeromicrobiome is thus poorly understood and difficult to predict due to the high heterogeneity of the airborne microorganisms and their properties, spatially and temporally. The atmosphere acts as a highly selective dispersion means on large scales for microbial cells, exposing them to a multitude of physical and chemical atmospheric processes. We provide here a brief critical review of the current knowledge and propose future research directions aiming at improving our comprehension of the atmosphere as a biome.